2006
DOI: 10.1530/rep.1.00770
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction mechanisms involved in in vitro ram sperm capacitation

Abstract: We validate the chlortetracycline (CTC) technique for the evaluation of capacitation and acrosome reaction-like changes in ram sperm, carrying out a double estimation of the acrosome status after treatment with lysophosphatidylcholine, using fluorescein isocyanate (FITC)-RCA/ethidium homodimer 1 (EthD-1) and CTC/EthD-1. Highly consistent results and a positive correlation between the results of acrosome-reacted sperm evaluated with both techniques were obtained. In this study, we evaluate the effects of ram sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 74 publications
(49 reference statements)
4
59
0
1
Order By: Relevance
“…Significant differences related to capacitated samples: already phosphorylated at tyrosine, serine and threonine residues in control samples ( Fig. 2A-C), as we have already reported at tyrosine (Perez-Pe et al 2002, Grasa et al 2006. We confirmed that in vitro capacitation promoted a significant increase in the content of some bands phosphorylated at tyrosine (Table 1) as reported previously (Grasa et al 2006).…”
Section: Protein Phosphorylation Associated With In Vitro Capacitatiosupporting
confidence: 90%
See 4 more Smart Citations
“…Significant differences related to capacitated samples: already phosphorylated at tyrosine, serine and threonine residues in control samples ( Fig. 2A-C), as we have already reported at tyrosine (Perez-Pe et al 2002, Grasa et al 2006. We confirmed that in vitro capacitation promoted a significant increase in the content of some bands phosphorylated at tyrosine (Table 1) as reported previously (Grasa et al 2006).…”
Section: Protein Phosphorylation Associated With In Vitro Capacitatiosupporting
confidence: 90%
“…As the proportion of capacitated sperm in control samples was not very high ( Fig. 1), this might have occurred either because phosphorylations started during the swim-up procedure, or because some proteins are constitutively phosphorylated in serine and/ or threonine residues, as already reported for tyrosine residues (Grasa et al 2006). After incubating in capacitating conditions, we detected a quantitative increase in the intensity of several bands, which indicates that ram sperm capacitation is also associated with protein Ser/Thr phosphorylation (Fig.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations